(untitled) (Acta Entomologica Serbica, 2023)
The survey was conducted during the period 2019-2022 in the vineyard areas of Diyarbakır, Mardin, Elazığ, Batman, and Şanlıurfa provinces. Studies were carried out to identify parasitoids of the wood-tissue pest Chlorophorus damascenus, which has recently become a problem in vineyard areas that are old and exposed to stress factors. Dolichomitus populneus (Ratzeburg, 1848) (Hymenoptera: Ichneumonidae), and Iphiaulax impostor (Scopoli, 1763) (Hymenoptera: Braconidae) were obtained from Chlorophorus damascenus. C. damascenus was a new host for D. populneus.